Clinical and Genealogical Research as a Method for Predicting the Development of Premature Ischemic Heart Disease - Oleg O. Zhurba; Oleksandr M. Hinhuliak (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. To establish the role of the hereditary factor in the risk of developing premature coronary heart disease (CHD) based on clinical and genealogical analysis of pedigrees.Materials and methods. The study included patients with CHD. The total sample size was 286 people, the mean age of the patients was 58.8 ± 2.9 years. The material for the analysis was the data of a clinical and genealogical analysis, which included the collection of data from the proband about the number of relatives with an indication of consanguinity. On the basis of the obtained data, pedigrees were compiled and the coefficient of family aggregation (FA) was calculated. A comparative analysis was conducted between experimental (n = 108, 25-44 years old) and control (n = 178, 75-90 years old) groups.Results. As a result of the analysis of pedigrees, it was established that in patients who had premature CHD, which developed at the age of 25-40 years, there was a FA of cardiovascular diseases, as evidenced by the determined frequency of the hereditary burden of family history for cardiovascular diseases of 50.9%. When compared with the corresponding frequency in the group of elderly patients, the determined frequency of family burden of 24.2% which was significantly lower than that in young patients, p = 0.0001; χ2 = 33.12. The calculated coefficient of FA was 2.1, which indicates that the risk of premature CHD is two times higher in families with a burdensome family history of cardiovascular diseases. Analysis of the burdensome history of cardiovascular diseases considering the degree of kinship with the proband established that in patients of both groups, the burdensome history was observed with the highest frequency in relatives of the 1st degree of kinship: 86.2% in the experimental and 83.3% in the control groups.Conclusions. It was found that in families with a burdensome family history of cardiovascular diseases, the risk of developing premature CHD is two times higher, as evidenced by the calculated coefficient of FA - 2.1; p = 0.0001; χ2 = 33.12. It was found that in both groups of the study, the prevalence of family history of cardiovascular diseases prevailed, mainly among relatives of the first degree of consanguinity.